Interventions and outcomes of patients with multiple myeloma receiving salvage therapy after BCMA-directed CAR T therapy - Oliver Van Oekelen; Karthik Nath; Tarek H. Mouhieddine; Tasmin Farzana; Adolfo Aleman; David T. Melnekoff; Yogita Ghodke‐Puranik; Gunjan L. Shah; Alexander M. Lesokhin; Sergio Giralt; Santiago Thibaud; Adriana Rossi; et al. (2022)
B-cell maturation antigen (BCMA)-directed chimeric antigen receptor T-cell (CAR T) therapy has demonstrated remarkable efficacy in patients with relapsed/refractory multiple myeloma, and now there are two US Food and Drug Administration-approved BCMA-directed CAR T products. However, despite high initial response rates, most patients eventually relapse. The outcomes of patients with disease recurrence after BCMA-directed CAR T have not been comprehensively studied, and such an analysis would help define optimal treatment strategies. We analyzed the salvage treatments and outcomes of 79 patients with multiple myeloma from two academic institutions, who had progression of disease after treatment with BCMA-directed CAR T. A total of 237 post-CAR T salvage treatment lines were used, and patients received a median of 2 (range, 1-10) treatment lines. The median overall survival from the date of relapse post-CAR T therapy was 17.9 months (95% confidence interval [CI], 14.0 non-estimable). The overall response rate to the first salvage regimen was 43.4%, with a median progression-free survival of 3.5 months (CI, 2.5-4.6). Thirty-five patients (44.3%) received a T-cell-engaging therapy (bispecific antibody or subsequent CAR T) as salvage treatment. The overall survival in patients who received subsequent T-cell-engaging therapy was not reached after a median follow up of 21.3 months. Patients with multiple myeloma who relapse after BCMA-directed CAR T have a limited prognosis but can be potentially treated with multiple lines of salvage therapy. T-cell-engaging therapies appear to maintain pronounced clinical activity in this setting.